(untitled) (Constructionism Conference Proceedings, 2025)
Logo programming is inseparable from constructionism. This workshop offers a hands-on crash course into the Logo philosophy, language design, range of possible projects, dialects, and pedagogical approaches applicable to Logo and its descendant environments. The emerging availability of computationally rich AI environments not only enrich learning adventures but benefit from the sorts of computational fluency developed by children engaged in Logo-like programming experiences. The workshop models pedagogical techniques essential for successful project-based learning in any curricular context, with or without computing.